2013
DOI: 10.1093/ptep/pts070
|View full text |Cite
|
Sign up to set email alerts
|

Tachyon vacuum of bosonic open string field theory in marginally deformed backgrounds

Abstract: We consider bosonic open string field theory in marginally deformed backgrounds, which is obtained by expanding the string field around the identity-based solutions associated with marginal deformations. We find a new set of string fields which satisfies the KBc algebra, but the nilpotent kinetic operator is that of the theory expanded around the identity-based marginal solution. By use of these string fields, we construct the tachyon vaccum solution in marginally deformed backgrounds. The vacuum energy densit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(47 citation statements)
references
References 33 publications
2
45
0
Order By: Relevance
“…Let us quickly review the structure of the solution, details can be found in [3]. It is derived from an identity-based solution, discovered years ago by Takahashi and Tanimoto [24], which is used here as an elementary identity-like string field in addition to the well known fields K, B, c. Calling Φ the TT solution [24], and defining as in [25]…”
Section: Review Of the Simple Marginal Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Let us quickly review the structure of the solution, details can be found in [3]. It is derived from an identity-based solution, discovered years ago by Takahashi and Tanimoto [24], which is used here as an elementary identity-like string field in addition to the well known fields K, B, c. Calling Φ the TT solution [24], and defining as in [25]…”
Section: Review Of the Simple Marginal Solutionmentioning
confidence: 99%
“…In particular, Wick theorem implies that we have In computing the above quadruple integral (two integrals along the boundary and two vertical integrals implicit in the J's) one finds out, by a mechanism analogous to [25], that the contribution from the f 2 -terms in J precisely cancels with a delta-function contribution coming from the boundary integral of the current correlator. This leaves us with a net result…”
Section: Review Of the Simple Marginal Solutionmentioning
confidence: 99%
“…Concrete examples of these 'far' solutions in OSFT have been presented in [10] and in [5] building on [11][12][13][14][15]. It is therefore an important question whether we can find these solutions in Siegel gauge as well.…”
Section: Introductionmentioning
confidence: 99%
“…This lack of linearity makes it difficult to see whether there exists a complete renormalization scheme consistent with the assumption (4b) using the approach in [1]. , equation (9). The difference is the gray strips, which are not covered using the latter choice.…”
Section: Setupmentioning
confidence: 99%
“…Earliest attempts to construct SFT solutions dealt mainly with finite boundary operators (for example, [2,3]), but the challenge due to singular operators has been mostly overcome: for marginal operators, in [1,4], and, for bcc operators, in several recent works, including [5,6,7]. Other approaches have also been considered in [8] and [9,10,11].…”
Section: Introductionmentioning
confidence: 99%